Побудова прогнозної моделі енерговитрат за допомогою застосування методу планування експерименту - Розен, Віктор Петрович; Ляпота, Ксенія Петрівна; Шокарьов, Дмитро Анатолійович (НТУ "ХПІ", 2010)
This article deals with analytical survey of existent forecasting methods. The forecasting model of products output depending on energy consumption indices that allow to analyze and minimize enterprise power in cost has been worked out.
Construction of look-ahead model of power expenses by means of application of a method of planning of experiment
Keywords: енергоспоживання; моделювання математичне; ресурси паливно-енергетичні; планування статичне